2017
DOI: 10.5941/myco.2017.45.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Resolution Multi-Locus Microsatellite Typing Method for Colletotrichum gloeosporioides

Abstract: Colletotrichum gloeosporioides is an economically important fungal pathogen causing substantial yield losses indifferent host plants. To understand the genetic diversity and molecular epidemiology of this fungus, we have developed a novel, high-resolution multi-locus microsatellite typing (MLMT) method. Bioinformatic analysis of C. gloeosporioides unannotated genome sequence yielded eight potential microsatellite loci, of which five, CG1 (GT)n, CG2 (GT1)n, CG3 (TC)n, CG4 (CT)n, and CG5 (CT1)n were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It has been shown previously that the inter-specific CAT fusion between C. lindemuthianum and C. gossypii, resulted in some hybrids, which exhibited phenotypic variations and one hybrid turned out to be most pathogenic isolate so far reported (Roca et al, 2004). We have also shown that Indian C. gloeosporioides isolates showed high levels of genetic diversity (Mehta et al, 2017).…”
Section: Introductionsupporting
confidence: 53%
“…It has been shown previously that the inter-specific CAT fusion between C. lindemuthianum and C. gossypii, resulted in some hybrids, which exhibited phenotypic variations and one hybrid turned out to be most pathogenic isolate so far reported (Roca et al, 2004). We have also shown that Indian C. gloeosporioides isolates showed high levels of genetic diversity (Mehta et al, 2017).…”
Section: Introductionsupporting
confidence: 53%
“…Among different species, C. gloeosporioides and C. siamense cause anthracnose in a wide range of host plants such as fruit, vegetable and ornamental plants (Cai et al, 2009;Freeman et al, 1996;Hyde et al, 2009;Jayawardena, 2018;Sharma et al, 2013). We have shown that there is a high level of genetic diversity in C. gloeosporioides isolates in India (Mehta et al, 2017). Our observation also corroborates with a series of studies published on genetic and pathogenic diversity of C. gloeosporioides (Denoyes-Rothan et al, 2003;Nova et al, 2011;Weeds et al, 2003).…”
Section: Introductionmentioning
confidence: 72%
“…Among different species, C. gloeosporioides and C. siamense cause infection in a wide range of host plants (Cai et al 2009 ; Freeman et al 1996 ; Hyde et al 2009 ; Jayawardena 2018 ; Sharma et al 2013 ). We have previously reported a high level of genetic diversity in C. gloeosporioides isolates in India (Mehta et al 2017 ). Our observation also corroborates with earlier studies which discussed genetic and pathogenic diversity in C. gloeosporioides (Denoyes-Rothan et al 2003 ; Nova et al 2011 ; Weeds et al 2003 ).…”
Section: Introductionmentioning
confidence: 98%